The effect of digital booklets “Crustaceae diversity at mangrove Sangiang Island” on students' conservation attitude using problem-based learning - Indria Wahyuni; Dwi Ratnasari; Mahrawi Mahrawi; Inayah Inayah (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
The rapid advancement of technology causes educators to be ready to use digital-based learning media. This study aims to determine the effect of the digital booklet on the diversity of mangrove crabs on Sangiang Island in the Problem Based Learning (PBL) model on students' conservation attitudes. This research method uses a quasi-experimental design with a post-test-only control group design. The research sample was taken using a purposive sampling technique. This study used two sample groups, namely the control and experimental groups. Data collection uses a questionnaire which is accessed via a Google form. The questionnaire contains questions about the conservation attitudes character of as many as 50 items; with a value scale from 1-4. The results showed an effect of using digital booklets on the conservation attitude of students at SMA Negeri 4 Serang City. The average conservation attitude in the experimental class got a fairly high score of 55, while the control class got a score of 54. This value is the result of the accumulation of five characteristics of attainment of conservation attitudes, namely knowledge, concern, skills, attitudes, and participation. Based on these results, using digital media, one of which is a booklet, can be a solution for achieving the competence of students' conservation attitudes.Abstrak Pesatnya kemajuan teknologi menyebabkan para pendidik harus siap memanfaatkan media pembelajaran berbasis digital. Penelitian ini bertujuan untuk mengetahui pengaruh booklet digital keanekaragaman kepiting bakau di pulau Sangiang dengan model Problem Based Learning (PBL) terhadap sikap konservasi siswa. Metode penelitian ini menggunakan quasi experiment dengan rancangan post-test only control group design. Pengambilan sampel penelitian menggunakan teknik purposive sampling. Penelitian ini menggunakan dua kelompok sampel yaitu kelompok kontrol dan eksperimen. Pengumpulan data menggunakan angket yang diakses melalui Google form. Angket berisi pertanyaan tentang karakter sikap konservasi sebanyak 50 butir soal, dan dilengkapi dengan skala nilai dari 1-4. Hasil penelitian menunjukkan adanya pengaruh penggunaan booklet digital terhadap sikap konservasi siswa di SMA Negeri 4 Kota Serang. Rata-rata sikap konservasi di kelas eksperimen mendapatkan nilai yang cukup tinggi yaitu sebesar 55 sedangkan untuk kelas kontrol memperoleh nilai 54. Nilai tersebut adalah hasil akumulasi dari lima karakter ketercapaian sikap konservasi yaitu pengetahuan, kepedulian, keterampilan, sikap, dan partisipasi. Berdasarkan hasil tersebut, penggunaan media digital salah satunya berbentuk booklet dapat menjadi solusi untuk ketercapaian kompetensi sikap konservasi peserta didik.